Evolutionary Success of Open Source Software: an Investigation into Exogenous Drivers - Beecher, Karl; Boldyreff, Cornelia; Capiluppi, Andrea; Rank, Stephen (Electronic Communications of the EASST, 2008)
The âsuccessâ of a Free/Libre/Open Source Software (FLOSS) project has often been evaluated through the number of commits made to its configuration management system, number of developers and number of users. Based on SourceForge, most studies have concluded that the vast majority of projects are failures. This paper argues that the relative success of a FLOSS project can depend also on the chosen forge and distribution. Given a random sample of 50 projects contained within a popular FLOSS forge (Debian, which is the basis of the successful Debian distribution), we compare these with a similar sample from SourceForge, using product and process metrics, such as size achieved and number of developers in- volved. The results show firstly that, depending on the forge of FLOSS projects, researchers can draw different conclusions regarding what constitutes a successful FLOSS project. Secondly, the projects included in the Debian distribution benefit, on average, from more evolutionary activity and more developers than the comparable projects on SourceForge. Finally, the Debian projects start to benefit from more activity and more developers from the point at which they join this distribution.